Increased left and right atrial volume indices are associated with decreased survival times post-cardiac arrest. (January 2022) - Ibrahim, Sami H.; Bilchick, Kenneth C.; Miller, Matthew S.; Blazek, Olivia J.; Strickling, Jarred E.; Elumogo, Comfort; Wharton, Robert C.; Patel, Paras; Ondigi, Olivia; Brady, William J.; Kwon, Younghoon; Mazimba, Sula
Abstract: Background: Left and right atrial volume indices (LAVI and RAVI) are markers of cardiac remodeling. LAVI and RAVI are associated with worse outcomes in other cardiac conditions. This study aimed to determine the associations of these atrial volume indices with survival time post-cardiac arrest. Methods: This was a single center, retrospective study of patients with a sudden cardiac arrest event during index hospitalization from 2014-2018 based on pre-arrest parameters. The analysis was stratified based on whether a pulseless ventricular tachycardia/ventricular fibrillation (pVT/VF) event or a pulseless electrical activity (PEA)/asystole event occurred. Cox proportional hazards regression and model selection with best subsets approach evaluated the association of atrial volume parameters with survival times in the context of other covariates. Results: Of 305 patients studied (64 ± 14 years, 37% female), the mean LAVI was 34.0 ± 15.8 mL/m 2 (based on 162 reliable measurements), and mean RAVI was 25.0 ± 15.6 mL/m 2 (based on 163 measurements). Increased atrial volume indices were most strongly associated with survival in patients who had sustained pVT/VF (LAVI HR 0.47, 95% CI 0.25–0.90, p = 0.020; RAVI HR 0.57, 95% CI 0.30–1.05, p = 0.074). In multivariable best subsets Cox regression with LAVI, RAVI, and 13 other scaled covariates, LAVI < 34 ml/m 2 was by far the best single predictor of survival (p < 0.0001), and the next best predictor was the absence of pulmonary hypertension. Conclusion: Among patients with cardiac arrest from ventricular arrhythmias, those with no more than mild left atrial enlargement pre-arrest by LAVI measurement had the best prognosis. Additional studies are indicated to validate the importance of this finding for clinical management decisions. Condensed abstract: In patients with sudden cardiac arrest associated with ventricular arrhythmias, a left atrial volume index (LAVI) < 34 mL/m 2 prior to the arrest had the strongest association with survival among fifteen candidate predictors. Pulmonary hypertension was more common in patients with an elevated right atrial volume index (RAVI), and the absence of pulmonary hypertension was the next best pre-arrest parameter predictive of survival. Larger studies are indicated to validate the use of LAVI for clinical management decisions in this condition.